Updating Ways and Enhancing Pain Management Efficiencies among Healthcare (The International Journal for Scientific Research, 2022)
Introduction: Understanding of the current landscape of interventions is important to enhance pain management competencies among healthcare professionals. This systematic review aimed to assess the prevalence and efficacy of interventions targeted at enhancing pain management competencies among healthcare professionals, with the goal of informing evidence-based practices and facilitating improvements in patient care. Methods: A comprehensive search strategy, tailored to electronic databases including PubMed, MEDLINE, Embase, and the Cochrane Library, was employed to systematically identify relevant studies until August 2023. Eligible studies, meeting specific criteria and published within the last 10 years, underwent a rigorous screening process, with inclusion based on primary research articles focused on pain management competencies among healthcare professionals. The subsequent data extraction and quality assessment, conducted by two independent reviewers, ensured a thorough and methodologically sound review of the literature. Results: The review included seven studies with diverse samples and interventions aimed at enhancing pain management competencies among healthcare professionals. The sample sizes varied from 82 to 358 participants, with an average improvement of 27% in sample knowledge representation. The interventions, spanning educational programs, simulation training, and collaborative strategies, demonstrated consistent effectiveness in improving knowledge and self-efficacy, with simulation training showcasing tangible improvements in practical skills and collaborative approaches leading to enhanced teamwork skills, quantified by a 40% improvement. The quantitative assessments revealed significant overall improvements, including a 23% increase in knowledge scores, a 28% rise in self-efficacy, and a 37% improvement in teamwork. Conclusions: Our study contributes to the existing literature by quantifying the substantial improvements observed in pain management competencies among healthcare professionals through diverse interventions, including educational programs, simulation training, and collaborative approaches, emphasizing the importance of a multifaceted strategy, with calculated odds ratios and percentages providing concrete measures for the development of evidence-based practices and educational strategies.
Keywords: Pain Management; Healthcare Professionals; Interventions; Competencies; Systematic Review